2000
DOI: 10.1159/000026660
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Voluntary Consumption of Nicotine by Rats

Abstract: The 2-bottle free-choice method was used to study the voluntary consumption of nicotine by rats. Rats consumed nicotine voluntarily at different, albeit quite consistent, amounts. Voluntary intakes were higher in younger than older rats, but were not affected by gender. A previously forced nicotine intake had no effect on a subsequent voluntary intake of nicotine in older but increased it in younger rats. Forced exposure to nicotine of pregnant and lactating rats did not increase the voluntary intake by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
9
29
0
Order By: Relevance
“…WKR actually decreased their subsequent voluntary consumption of nicotine and both strains reduced their cocaine choice. In SpragueDawley rats we have shown previously that forced exposure did not increase a subsequent voluntary choice of any of the 4 substances tested here but actually had no effect on a subsequent free choice [23,28]. Thus, results of forced intake might also differ genetically.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…WKR actually decreased their subsequent voluntary consumption of nicotine and both strains reduced their cocaine choice. In SpragueDawley rats we have shown previously that forced exposure did not increase a subsequent voluntary choice of any of the 4 substances tested here but actually had no effect on a subsequent free choice [23,28]. Thus, results of forced intake might also differ genetically.…”
Section: Discussionmentioning
confidence: 59%
“…This is in agreement with York and Chan [18], who also observed different ethanol responses in BNR, or Little et al [22], who found older rats to be more sensitive to the effects of ethanol. In Sprague-Dawley rats, we found younger rats to consume voluntarily more nicotine than older rats [23]. This might explain the common observation that more young people start to experiment with both drugs and that some loose interest shortly thereafter.…”
Section: Discussionmentioning
confidence: 65%
“…This study more closely resembles the situation in humans who may use both drugs at the same time. This two-or three-bottle freechoice method has been used widely for ethanol, but has now been shown to be also valid for nicotine and other drugs as well [e.g., 5,8,9,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…dissolved easily in water, had a high-salt base and comparable pH, and was stable over extended periods of time). Other studies have relied on a direct comparison to water [21] , sweetened solutions [33] and/or varying levels of nicotine concentration [29] .…”
Section: Chemicalsmentioning
confidence: 99%
“…For decades 2-bottle tests have been the procedure of choice for evaluating reactions to taste solutions [25][26][27] , including oral nicotine [18,21,28] in nonhumans. One of the serious challenges encountered by those using the 2-bottle choice method of nicotine selfadministration in rats has been to demonstrate that rats will voluntarily consume sufficient amounts of a solution containing nicotine [29] to reach levels necessary to exert a pharmacological effect.…”
Section: Introductionmentioning
confidence: 99%